Vitamin D stimulates Il-15 synthesis in rodent muscle - Ewendt, Franz; Drewitz, Fabienne; Althammer, Michael; Eichler, Cosima; Brandsch, Corinna; Brey, Stefanie; Winkler, Thomas; Wilkens, Mirja R.; St-Arnaud, René; Kreutz, Marina; Stangl, Gabriele I. (Biochemistry and Biophysics Reports, 2025)
Besides its classical skeletal function, vitamin D plays a critical role in both skeletal muscle and the immune system. Interleukin-15 (IL-15), which is highly expressed, and secreted complexed with its receptor, IL-15Rα, by skeletal muscle, stimulates the development of immune cells and affects myogenesis and muscle mass. However, little is known about possible regulators of this myokine. To test whether vitamin D could be a regulator of muscle IL-15 and IL-15Rα expression, C2C12 myotubes were treated with vitamin D3 metabolites and analysis were performed in gastrocnemius muscles of rats treated with a single intraperitoneal dose of 1,25(OH)2D3. The role of VDR was investigated by siRNA technique in C2C12 myotubes and in gastrocnemius muscles of vitamin D receptor knockout (Vdr-KO) mice. Treatment of C2C12 myotubes with 1,25(OH)2D3 or 25(OH)D3 increased Il-15 gene expression in a dose-dependent manner and 1,25(OH)2D3 also moderately increased the relative Il-15 protein amount. Rats treated with a single dose of 1,25(OH)2D3 demonstrated a higher mRNA abundance of muscle Il-15 than controls. The 1,25(OH)2D3 effect on Il-15 was considerably weaker in C2C12 myotubes treated with Vdr-specific siRNA. Vdr-KO mice showed significantly lower muscle Il-15 mRNA than WT mice. Il-15Ra mRNA and Il-15/Il-15Rα protein abundance were unaffected by 1,25(OH)2D3-treatment or VDR functionality, and Cyp27b1 activity is not required for 25(OH)D3-mediated Il-15 gene expression. The results provide evidence for a regulatory role of hydroxyvitamin D3 metabolites on the Il-15 synthesis in skeletal muscle cells, which is largely mediated by the VDR.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Calcitriol; Cytokine; Immune system; Immunosenescence; Muscle-immune-crosstalk; Vitamin D receptor